A novel architecture to classify histopathology images using convolutional neural networks - Kandel, Ibrahem (2020)
Kandel, I., & Castelli, M. (2020). A novel architecture to classify histopathology images using convolutional neural networks. Applied Sciences (Switzerland), 10(8), 1-17. [2929]. https://doi.org/10.3390/APP10082929